1984
DOI: 10.1016/0006-3207(84)90088-0
|View full text |Cite
|
Sign up to set email alerts
|

Some long-term observations on cyclical and seral processes in Dutch heathlands

Abstract: Changes over a period of 10 30 years in the vegetation of some INTRODUCTI ONMost of the ericaceous vegetation in Europe is situated in man-made heathlands. These heathlands are maintained by management practices, such as burning, mowing or cutting sods, which remove the standing crop and in the last case also the organic matter accumulated in the Ao-horizon (Gimingham, 1972). These practices lead to the development of even-aged 283 Biol. Conserz~.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…In the untreated plots (X) virtually no changes in the vegetation were observed, except for the dying of Deschampsia tussocks. This was found to be a temporary phenomenon, typical for an ungrazed Deschampsia grass heath (Diemont & Heil 1984). Prescribed burning in the Kootwijk site (September, 1978(September, -1980 did not bring about any change in the dominance of Molinia.…”
Section: Study Sites and Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In the untreated plots (X) virtually no changes in the vegetation were observed, except for the dying of Deschampsia tussocks. This was found to be a temporary phenomenon, typical for an ungrazed Deschampsia grass heath (Diemont & Heil 1984). Prescribed burning in the Kootwijk site (September, 1978(September, -1980 did not bring about any change in the dominance of Molinia.…”
Section: Study Sites and Methodsmentioning
confidence: 95%
“…Which kinds of grass species are involved in the seral change depends on soil type and geomorphic position (Diemont & Heil 1984). In-depth studies related to plant nutrients involved in these changes can be found in Heil (1984) and Berendse (1985).…”
Section: Introductionmentioning
confidence: 99%
“…Molinia (purple moor grass) abundance has increased at the expense of Calluna (heather or ling) since the start of the industrial revolution in upland areas of England and Wales and in parts of southern and western Scotland (Chambers, Dresser & Smith 1979), and anecdotal accounts indicate that increases have continued over the last 20–30 years. Increases in Molinia have also been found elsewhere in Europe, where large areas of Dutch heathlands have been colonized by Molinia at the expense of dwarf shrub vegetation (Heil & Diemont 1983; Diemont & Heil 1984).…”
Section: Introductionmentioning
confidence: 88%
“…These observed shifts in vegetation composition from Calluna to Molinia have been variously attributed to inappropriate burning and/or grazing regimes (Grant, Hunter & Cross 1963; Miller, Miles & Heal 1984; Grant & Maxwell 1988) and increased atmospheric nitrogen and sulphur deposition, especially in Holland (Chambers, Dresser & Smith 1979; Heil & Diemont 1983; Diemont & Heil 1984; Lee et al . 1987; Hogg, Squires & Fitter 1995; Roem, Klees & Berendse 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Management of heathlands is required to maintain these cultural landscapes and in the past this management occurred on a 3-4 yr cycle (Webb, 1998). Currently, this cycle length has extended or is non-existent (Diemont and Heil, 1984;Wessel et al, 2004). From the perspective of optimizing C uptake and minimizing C output, having an understanding the C dynamics of these ecosystems allows us to determine the optimum time to cut the vegetation, thus contributing to global C emission mitigation measures.…”
Section: Annual Soil C Loss and Links To Global Changementioning
confidence: 99%